HUBUNGAN KECERDASAN EMOSIONAL DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PKN KELAS II - Ulum, Ilham Rahayu (Joyful Learning Journal, 2017)
Tujuan penelitian ini adalah mengetahui hubungan kecerdasan emosional dan motivasi belajar terhadap hasilbelajar PKn. Penelitian ini menggunakan metode kuantitatif, desain penelitian korelasional. Populasi sebanyak 187siswa. Teknik pengambilan sampel menggunakan Proposionate Stratified Random Sampling, diperoleh sampel 126siswa. Teknik pengumpulan data menggunakan tes, angket, wawancara dan dokumentasi. Teknik analisis datamenggunakan analisis deskripstif, teknik analisis korelasi sederhana dan teknik analisis korelasi ganda. Hasilanalisis deskriptif menunjukkan kecerdasan emosional, motivasi belajar dan hasil belajar PKn dalam kategorisedang. Hasil analisis korelasi menunjukkan hubungan yang sangat kuat antara kecerdasan emosional terhadaphasil belajar PKn. Motivasi belajar mempunyai hubungan sangat kuat terhadap hasil belajar PKn. Kecerdasanemosional dan motivasi belajar secara bersama-sama berhubungan terhadap hasil belajar PKn dalam kategorisangat kuat. Simpulan penelitian ini terdapat hubungan yang positif dan signifikan antara kecerdasan emosionaldan motivasi belajar terhadap hasil belajar PKn siswa kelas II SD Gugus Gajahmada Kecamatan GajahmungkurKota Semarang. The purpose of this study was to determine the relationship of emotional intelligence and learning motivationtowards the learning achievement of PKn Subject. This study used quantitative approach and correlational researchdesign. The population involved were 187 students. Meanwhile the sampling technique used was ProportionateStratified Random Sampling. By this sampling technique, it was obtained 126 sample of students. From thesesample, the data were collected by using tests, questionnaires, interviews and documentation. Further, the dataanalysis techniques used were descriptive analysis, simple correlation analysis techniques and multiple correlationanalysis techniques. The results of descriptive analysis showed that emotional intelligence, learning motivation andthe learning achievement of PKn Subject were in the medium category. On the other hand, the result of correlationanalysis showed a very strong correlation between emotional intelligence and the learning achievement of PKnSubject. The same result was also obtained in the correlation between learning motivation with the learningachievement of PKn Subject. The last, emotional intelligence and learning motivation were together related to thelearning achievement of PKn Subject in very strong categories. The conclusion of this study was that there was apositive and significant relationship between emotional intelligence and learning motivation toward the learningachievement of PKn Subject by the second grade students of Elementary Schools Cluster Gajahmada,Gajahmungkur Subistrict, Semarang City.